Unlocking Scientific Reasoning through Ethno-STEM : Mapping the Research Landscape and Future Directions - Ina Ana Khoeriah; Della Apriyani Kusuma Putri; Andini Retno Yunitasari (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The stagnation of global scientific literacy scores, as highlighted by PISA results, necessitates a paradigm shift toward culturally responsive pedagogies that foster holistic competencies. This study investigates the global trends of Ethno-STEM integration in facilitating Scientific Reasoning and 6C Skills (Character, Citizenship, Collaboration, Communication, Creativity, and Critical Thinking) through the lens of deep learning. Employing a mixed-method approach combining Systematic Literature Review (SLR) with PRISMA protocol and bibliometric analysis, we analyzed 2889 documents from the Scopus database spanning 2015 to 2026. The findings reveal an exponential growth in publications, predominantly driven by Indonesia and the United States, indicating a shift from a